Comparison of Moora, Waspas and SAW Methods in Decision Support Systems - Samuel Van Basten Halomoan Manurung; Indra M Sarkis Simamora; Herlina Allagan (Institute of Computer Science (IOCS), 2021)
Education is a process in the framework that can adapt to the environment and thus will cause changes in themselves that enable it to involve all that is in society. In this case, the process of selecting the best teachers and staff in data processing is still done manually by conducting tests through several criteria that have been made. Criteria used for the process. There are 19 criteria. The selection process carried out manually has several weaknesses so that it will result in errors in data processing. For this reason, a Decision Support System is needed that can be used in the process of selecting the best Teachers and Staff. In this study, using the calculation method calculation methods Moora, SAW, and WASPAS with scholarship recipients. The results obtained from the Moora Method are 3 (three) highest values at V1 = 1.89; V8 = 1.81; and V2 = 1.80, the SAW Method was 3 (three) highest values at V1 = 10.38; V8 = 9.90; and V2 = 9.87. The WASPAS method that 3 is highest at V1 = 5.07; V8 = 4.72; and V2 = 4.68. The system created using the SAW method because it provides the Best Alternative value and provides the best ranking results